Exploring differences in substance use and attachment patterns amongst offending populations - Stokes, Anna Maria (2018)
There appears to be a link between substance abuse and offending behaviour; however, other risk factors are likely to interact with this, and it is unclear how these factors relate to sexual offending. This thesis explored substance use and attachment patterns in sexual offenders compared to other offending and non-offending populations. It also considered the impact of these risk factors on treatment readiness, motivation to change, engagement and therapeutic alliance, and risk of future offending.